2023
DOI: 10.3390/ijms24043972
|View full text |Cite
|
Sign up to set email alerts
|

Cell Type-Specific Anti-Viral Effects of Novel SARS-CoV-2 Main Protease Inhibitors

Abstract: Recently, we have described novel pyridyl indole esters and peptidomimetics as potent inhibitors of the severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) main protease. Here, we analysed the impact of these compounds on viral replication. It has been shown that some antivirals against SARS-CoV-2 act in a cell line-specific way. Thus, the compounds were tested in Vero, Huh-7, and Calu-3 cells. We showed that the protease inhibitors at 30 µM suppress viral replication by up to 5 orders of magnitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…First, we analyzed whether AKS461 would suppress SARS-CoV-2 similarly to C6-ceramides. Since we and others have described that compounds inhibit SARS-CoV-2 replication in a cell line-specific way, three different cell lines were analyzed [ 7 ]. Thus, the cytotoxicity of AKS461 was analyzed by determining the cell growth rate after 72 h in Vero and Huh-7 cells as described before [ 7 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…First, we analyzed whether AKS461 would suppress SARS-CoV-2 similarly to C6-ceramides. Since we and others have described that compounds inhibit SARS-CoV-2 replication in a cell line-specific way, three different cell lines were analyzed [ 7 ]. Thus, the cytotoxicity of AKS461 was analyzed by determining the cell growth rate after 72 h in Vero and Huh-7 cells as described before [ 7 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since we and others have described that compounds inhibit SARS-CoV-2 replication in a cell line-specific way, three different cell lines were analyzed [ 7 ]. Thus, the cytotoxicity of AKS461 was analyzed by determining the cell growth rate after 72 h in Vero and Huh-7 cells as described before [ 7 , 29 ]. Similarly, MTT assays were performed after 72 h in Calu-3 cells since automated cell counting failed with this cell line [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The antiviral landscape was obviously dominated by SARS-CoV-2 studies. Interesting SARS-CoV-2 main protease inhibitors were reported by Geiger et al [ 45 ], whereas Ma et al [ 46 ] identified darunavir derivatives which effectively inhibit the cysteine-like protease of this virus. Many studies on monoclonal antibodies targeting various proteins of the virus were also ultimately published [ 47 , 48 , 49 , 50 , 51 ], although the role of these therapeutics in the management of COVID-19 was very much re-dimensioned due to mutations and loss of efficacy as well as the design of small molecule inhibitors targeting various viral proteins [ 52 , 53 ].…”
Section: State Of the Artmentioning
confidence: 99%